The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0149838
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tram Stent Method in the Treatment of Coronary Bifurcation Lesions – Finite Element Study

Abstract: A novel stent was designed for the treatment of coronary bifurcation lesion, and it was investigated for its performance by finite element analysis. This study was performed in search of a novel method of treatment of bifurcation lesion with provisional stenting. A bifurcation model was created with the proximal vessel of 3.2 mm diameter, and the distal vessel after the side branch (2.3 mm) was 2.7 mm. A novel stent was designed with connection links that had a profile of a tram. Laser cutting and shape settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Taeksu and Jang 21 explored the interactions of several stent types and arteries with different curvatures (0, 0.2, and 0.4) and indicated the recovery of stenotic artery. Similar studies have also been conducted as reported in Conway et al, 22 Morlacchi et al, 23 Ragkousis et al, 24 Schiavone and Zhao, 25 Arokiaraj et al, 26 Wei et al 27…”
Section: Introductionsupporting
confidence: 81%
“…Taeksu and Jang 21 explored the interactions of several stent types and arteries with different curvatures (0, 0.2, and 0.4) and indicated the recovery of stenotic artery. Similar studies have also been conducted as reported in Conway et al, 22 Morlacchi et al, 23 Ragkousis et al, 24 Schiavone and Zhao, 25 Arokiaraj et al, 26 Wei et al 27…”
Section: Introductionsupporting
confidence: 81%
“…As Mg is a potential material for the stent applications, in this section, we are going to focus mainly on the application of FEA in the stent industry. Many researchers used this powerful tool to predict the performance of stents made of different materials including polymeric stents, Nitinol stents, stainless steel stents, and BMG‐based stents to name a few. FEA is in practice to analyze Mg stents for their mechanical performance and corrosion behavior.…”
Section: Computational Modelsmentioning
confidence: 99%
“…Geometric modelling of biological structures by using tools based on computer-aided design (CAD) is currently applied to disease diagnosis [10,11], design of medical devices [12,13], and geometric reconstruction for different purposes [14,15]. More specifically, in the field of ophthalmology, there are several studies that use CAD methods to develop the concept of a patient-specific model [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%